Assessing the Fatigue Related Psychological Risk Factors among Oil and Gas Tankers Drivers in Malaysia - Sabir, Asrar Ahmed; B. Isha, Ahmad Shahrul Nizam (International Review of Management and Marketing, 2016)
The oil and gas sector plays a vital role in the economic development of Malaysia. The transportation of oil and gas product is a sensitive issue because a minor negligence of a tanker truck driver can cause a serious accident of heavy loss and fatality. To address this issue, the study of oil and gas truck drivers' Fatigue is very important because most of the transportation activities depend on them. Further, the psychological risk factors (personality traits, behaviors and work stress) have a high impact on drivers' fatigue. The annual report has been taken from Malaysian Institute of Road Safety Research (MIROS). The report has identified the fatalities rate among heavy vehicle drivers. Several fatal crashes' results show the high fatalities rate in Malaysia. The concepts of mental fatigue, physical fatigue, task-related fatigue and socioeconomic impacts of drivers' fatigue are discussed in this study. In conclusion, the proposed methodology and future recommendations are presented. Keywords: Psychological risk factors; Drivers fatigue; tanker drivers JEL Classification: R41